Psycho-perceptual-motor skills are deemed critical to save the penalty corner in international field hockey. (November 2020) - Morris-Binelli, Khaya; van Rens, Fleur E.C.A.; Müller, Sean; Rosalie, Simon M.
Abstract: In interceptive sports such as field hockey goalkeeping, the psycho-perceptual-motor skill anticipation is vital for performance due to the extreme time constraints associated with saving a goal. The purpose of this study was to understand the beliefs and attitudes of international field hockey goalkeepers and coaches regarding anticipation of the drag-flick in penalty corners. Seven international goalkeepers and five international coaches were interviewed. Using a constructionist and relativist approach to reflexive thematic data analysis, we identified three overarching themes to anticipate the drag-flick, namely, pre-match video analysis, perception and action, and psychological factors. In the first theme, participants reported that pre-match video analysis allowed goalkeepers and coaches to identify the attacking capabilities of opposing teams. This analysis was used to inform defensive structure and save the drag-flick. In the second theme, participants reported that perception and action, which consisted of the pick-up of visual cues and movement execution, was important to anticipate the drag-flick. Goalkeepers reported that they rely heavily on ball flight, which was central in coaches' approaches in training drills such as to use a projection machine that presents only ball flight information. The third theme, psychological factors, encompassed, psychological resilience, arousal regulation, leadership and communication, and sports intelligence, which were thought to be vital to facilitate anticipation of the drag-flick. The findings of this study have important implications for how to assess and train visual anticipation in time-constrained interceptive sports skills. Highlights: Psycho-perceptual-motor factors such as anticipation is vital to save a drag-flick. Pre-match video analysis is deemed important for goalkeepers' preparation. The pick-up of visual cues and movement execution are key to save a drag-flick. Psychological factors are thought to affect penalty corner saving performance. An interdisciplinary approach is recommended to investigate sport performance.